Opportunities for nanomaterials in more sustainable aviation - Afshin Pendashteh; Anastasiia Mikhalchan; Tamara Blanco Varela; Juan J. Vilatela (Discover Nano, 2024)
Abstract New materials for electrical conductors, energy storage, thermal management, and structural elements are required for increased electrification and non-fossil fuel use in transport. Appropriately assembled as macrostructures, nanomaterials can fill these gaps. Here, we critically review the materials science challenges to bridge the scale between the nanomaterials and the large-area components required for applications. We introduce a helpful classification based on three main macroscopic formats (fillers in a matrix, random sheets or aligned fibres) of high-aspect ratio nanoparticles, and the corresponding range of bulk properties from the commodity polymer to the high-performance fibre range. We review progress over two decades on macroscopic solids of nanomaterials (CNTs, graphene, nanowires, etc.), providing a framework to rationalise the transfer of their molecular-scale properties to the scale of engineering components and discussing strategies that overcome the envelope of current aerospace materials. Macroscopic materials in the form of organised networks of high aspect ratio nanomaterials have higher energy density than regular electrodes, superior mechanical properties to the best carbon fibres, and electrical and thermal conductivity above metals. Discussion on extended electrical properties focuses on nanocarbon-based materials (e.g., doped or metal-hybridised) as power or protective conductors and on conductive nanoinks for integrated conductors. Nanocomposite electrodes are enablers of hybrid/electric propulsion by eliminating electrical transport limitations, stabilising emerging high energy density battery electrodes, through high-power pseudocapacitive nanostructured networks, or downsizing Pt-free catalysts in flying fuel cells. Thermal management required in electrified aircraft calls for nanofluids and loop heat pipes of nanoporous conductors. Semi-industrial interlaminar reinforcement using nanomaterials addresses present structural components. Estimated improvements for mid-range aircraft include > 1 tonne weight reduction, eliminating hundreds of CO2 tonnes released per year and supporting hybrid/electric propulsion by 2035.